Iridium single atom modified cobalt hydroxide nanosheet and preparation method and application thereof
By irradiating the loaded iridium single atoms with ultraviolet light on the amorphous cobalt hydroxide nanosheets, the problems of harsh and high cost of synthesis of existing electrocatalytic water decomposition catalyst materials are solved, and the problems of harsh conditions and high cost are improved. It has catalytic efficiency and activity, and is suitable for large-scale applications.
Patent Information
- Application Number
- CN202310053758.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-03
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-02-03
AI Technical Summary
The synthesis conditions of existing catalyst materials for electrocatalytic water decomposition and oxygen production are harsh and costly, which limits their wide application. The kinetics of the oxygen evolution reaction are slow, affecting efficiency.
Amorphous cobalt hydroxide nanosheets are used as a carrier, and the iridium is uniformly loaded on its surface in a single atom form through ultraviolet light irradiation, forming cobalt hydroxide nanosheets modified with iridium single atoms, simplifying the synthesis process and reducing costs.
It improves the activity and utilization rate of the catalyst, enhances the efficiency of electrocatalytic water decomposition and oxygen production, reduces the overpotential, and is simple and controllable, suitable for large-scale production.
Smart Images

Figure CN116005193B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst materials, and in particular to a cobalt hydroxide nanosheet modified with a single iridium atom, and a preparation method and application thereof. Background Art
[0002] As a clean and renewable energy carrier, hydrogen is expected to become an alternative to fossil fuels and provide an environmentally friendly solution to reduce carbon dioxide emissions. Among the many hydrogen production pathways, electrocatalytic water splitting is considered to be a sustainable way to achieve large-scale hydrogen production. However, due to its slow kinetics, the oxygen evolution reaction, one of the two half reactions of electrocatalytic water splitting, is considered to be the main bottleneck limiting the efficiency of electrocatalytic water splitting. Therefore, there is an urgent need to develop highly active electrocatalysts for oxygen production by electrocatalytic water splitting.
[0003] Prior art studies have pointed out that amorphous materials have local structural flexibility and abundant coordination unsaturated sites, which can accelerate charge transfer and promote the adsorption and diffusion of reactants. In addition, iridium is a metal with high catalytic activity for electrocatalytic water decomposition to produce oxygen, but its scarcity and high cost limit its widespread commercial application.
[0004] In order to solve the above technical problems, Yi Cui et al. from Stanford University reported a material for electrocatalytic water decomposition and oxygen production. First, Ni9Fe hydroxide (Ni9FeOOH) and 0.1 mg / mL of IrCl3(H2O)3 were dispersed in water, and then the mixed solution was quickly frozen into ice cubes with liquid nitrogen under dark conditions. Subsequently, the frozen ice cubes were placed on a cooling table and exposed to ultraviolet light, kept at minus 35°C for 1 hour, to form single atomic iridium dispersed on the Ni9FeOOH substrate. However, the synthesis conditions of the catalyst material are harsh, liquid nitrogen is required for pre-freezing, and the entire ultraviolet illumination process needs to be maintained at a low temperature (-35°C) for operation, which increases the cost and is not conducive to popularization and use.
[0005] To this end, the present invention provides a cobalt hydroxide nanosheet modified with a single iridium atom, and a preparation method and application thereof. Summary of the invention
[0006] In order to solve the above-mentioned deficiencies in the prior art, the present invention provides a cobalt hydroxide nanosheet modified with a single iridium atom, and a preparation method and application thereof.
[0007] The iridium single atom-modified cobalt hydroxide nanosheet and its preparation method and application are achieved by the following technical solutions:
[0008] The first object of the present invention is to provide a method for preparing iridium single atom-modified cobalt hydroxide nanosheets, comprising the following steps:
[0009] Step 1, using amorphous cobalt hydroxide nanosheets as a precursor, and uniformly dispersing them in a water solvent A to obtain a solution A;
[0010] Step 2, adding an iridium source to solution A and mixing evenly to obtain solution B;
[0011] Step 3, subjecting the solution B to ultraviolet irradiation treatment, so that the metal iridium is loaded on the amorphous cobalt hydroxide nanosheets in the form of single atoms, to obtain a mixture A;
[0012] Step 4, after solid-liquid separation of the mixture A, a solid component A is obtained, and the solid component A is sequentially washed and freeze-dried to obtain the iridium single atom-modified cobalt hydroxide nanosheets.
[0013] Furthermore, the usage ratio of the amorphous cobalt hydroxide nanosheets to the aqueous solvent A is 0.8-1.2 mg:1 mL.
[0014] Furthermore, the iridium source is iridium chloride.
[0015] Furthermore, the usage ratio of the iridium source to the amorphous cobalt hydroxide nanosheets in the solution A is 0.005-0.03 mmol:50 mg.
[0016] Furthermore, the ultraviolet light irradiation treatment time is 0.5 to 1.5 hours.
[0017] Furthermore, the amorphous cobalt hydroxide nanosheets are prepared by the following steps:
[0018] S1, uniformly dispersing the cobalt salt in the aqueous solvent B, then adding NaBH4 and mixing evenly to obtain a mixture B;
[0019] S2, separating the mixture B into solid and liquid to obtain a solid component B, washing the solid component B and freeze-drying it to obtain the amorphous cobalt hydroxide nanosheets.
[0020] Furthermore, the cobalt salt is cobalt chloride or cobalt nitrate.
[0021] Further, the usage ratio of the cobalt salt to the aqueous solvent B is 0.8-1.2 mmol:100 mL;
[0022] The molar ratio of the NaBH4 to the cobalt salt is 3 to 5:1.
[0023] The second object of the present invention is to provide a cobalt hydroxide nanosheet modified with iridium single atoms prepared by the above-mentioned preparation method, wherein the cobalt hydroxide nanosheet modified with iridium single atoms comprises an amorphous cobalt hydroxide nanosheet and an iridium single atom on the amorphous cobalt hydroxide nanosheet.
[0024] The third object of the present invention is to provide an application of the above-mentioned iridium single atom modified cobalt hydroxide nanosheets in an electrocatalytic water decomposition oxygen production catalyst.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention uses amorphous cobalt hydroxide nanosheets as carriers and iridium as a load material, and uniformly loads iridium in the form of single atoms on the surface of the amorphous cobalt hydroxide nanosheets through a simple photodeposition method, thereby obtaining a composite material composed of ultra-thin amorphous cobalt hydroxide nanosheets and iridium single atoms modified on the nanosheets, i.e., iridium single-atom modified cobalt hydroxide nanosheets. The method of the present invention is simple to operate, has mild reaction conditions, is controllable and efficient in preparation, can be synthesized in large quantities, is energy-saving and cost-saving, and is conducive to popularization and use.
[0027] The iridium single atom-modified cobalt hydroxide nanosheet prepared by the present invention presents the morphology of a curled nanosheet, which is conducive to the exposure of active sites; and in the iridium single atom-modified cobalt hydroxide nanosheet prepared by the present invention, the amorphous cobalt hydroxide nanosheet has the advantages of local structural flexibility and abundant coordination unsaturated sites, which can accelerate charge transfer, and then can provide abundant anchoring sites for iridium atoms, providing a good basis for charge transfer. And wherein, iridium exists only in the form of a single atom on the surface of the cobalt hydroxide nanosheet, and iridium neither forms clusters or particles, nor is it incorporated into the deep interior of the cobalt hydroxide nanosheet, thereby increasing the exposure ratio of iridium atoms, increasing the number of active sites, and thereby improving the utilization rate of metal iridium.
[0028] When the iridium single atom-modified cobalt hydroxide nanosheet prepared by the present invention is used as a catalyst, the utilization rate of the active metal iridium in the process of electrocatalytic water decomposition and oxygen production can be improved while maintaining high performance of electrocatalytic water decomposition and oxygen production, thereby improving catalytic efficiency. And when it is used as a catalyst for electrocatalytic water decomposition and oxygen production, it can efficiently catalyze the electrocatalytic water decomposition and oxygen production and evolution reaction, and has a lower overpotential at the same current density compared with commercial catalysts. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 XRD patterns of the materials of Examples 1 to 4 and Comparative Example 2 of the present invention;
[0030] Figure 2 TEM image of the material of Example 3 of the present invention;
[0031] Figure 3 This is a high-angle annular dark field image-scanning transmission electron microscope (HAADF-STEM) image of the material of Example 3 of the present invention;
[0032] Figure 4It is the energy spectrum image of the material of Example 3 of the present invention;
[0033] Figure 5 Polarization curves of the materials of Examples 1-4, Comparative Example 1 and Comparative Example 2 of the present invention when used as anode catalysts for electrocatalytic water decomposition and oxygen production. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0035] The present invention provides a cobalt hydroxide nanosheet modified with a single iridium atom, and the preparation method thereof is as follows:
[0036] Step 1, using amorphous cobalt hydroxide nanosheets as a precursor, and uniformly dispersing them in a water solvent A to obtain a solution A;
[0037] It should be noted that the present invention does not limit the specific dispersion method of the amorphous cobalt hydroxide nanosheets in the aqueous solvent A, as long as the amorphous cobalt hydroxide nanosheets can be uniformly dispersed in the aqueous solvent A to form a solution A with uniform components, and the amount ratio of the amorphous cobalt hydroxide nanosheets to the aqueous solvent A is 0.8-1.2 mg:1 mL.
[0038] In order to improve the catalytic performance of the material, the present invention preferably uses amorphous cobalt hydroxide nanosheets as a precursor, and accelerates charge transfer and promotes the adsorption and diffusion of reactants due to the local structural flexibility and abundant coordination unsaturated sites of the amorphous material, thereby facilitating the electrocatalytic reaction. And the present invention preferably uses the amorphous cobalt hydroxide nanosheets prepared by the following steps (S1-S2) as a precursor:
[0039] S1, uniformly dispersing the cobalt salt in the aqueous solvent B, then adding NaBH4 and mixing evenly to obtain a mixture B;
[0040] The present invention uses NaBH4 to rapidly reduce and precipitate cobalt ions.
[0041] The present invention does not limit the specific type of cobalt salt, as long as it can provide cobalt ions, it can be selected from cobalt chloride or cobalt nitrate. The present invention does not limit the specific dispersion method of the cobalt salt in the aqueous solvent B, as long as the amorphous cobalt hydroxide nanosheets can be uniformly dispersed in the aqueous solvent A to form a solution with uniform components. The present invention preferably disperses in a stirring manner, at room temperature, according to the amount ratio of cobalt salt to aqueous solvent B of 0.8 to 1.2 mmol: 100 mL, the cobalt salt is added to the corresponding volume of aqueous solvent, and stirred at a stirring rate of 600 to 800 r / min for 15 to 25 min.
[0042] The molar ratio of the above-mentioned NaBH4 to the cobalt salt is 3 to 5:1, and in order to make the contact between NaBH4 and the cobalt salt more complete, NaBH4 is added in the form of a solution, and stirring is continued after addition, and stirring is carried out at a stirring rate of 600 to 800 r / min for 25 to 35 minutes.
[0043] S2, separating the mixture B into solid and liquid to obtain a solid component B, washing the solid component B and freeze-drying it to obtain amorphous cobalt hydroxide nanosheets;
[0044] The present invention does not limit the specific type of solid-liquid separation, as long as the solid component can be obtained, for example, by centrifugation at a speed of 8000 r / min for 1 min.
[0045] In order to avoid agglomeration of the cobalt hydroxide nanosheets during heating and drying, the present invention preferably adopts freeze drying to facilitate the dispersion of the cobalt hydroxide nanosheets in later use, and the freeze drying temperature is -45 to -25°C and the time is 12 to 36 hours.
[0046] Step 2, adding an iridium source to solution A and mixing evenly to obtain solution B;
[0047] It should be noted that the present invention does not limit the specific type of the iridium source, as long as it can provide iridium ions, and can be selected from IrCl3·xH2O, and the molar ratio of the iridium source to the amorphous cobalt hydroxide nanosheets is 0.005-0.03:1.
[0048] In order to make the iridium source fully and evenly contact with the amorphous cobalt hydroxide nanosheets, the present invention preferably adds the iridium source to solution A in the form of a solution to obtain solution B. The present invention does not limit the specific dispersion method of the iridium source in solution A, as long as the iridium source can be fully contacted with the amorphous cobalt hydroxide nanosheets in the aqueous solution A to form a solution with uniform components.
[0049] Step 3, subjecting solution B to ultraviolet irradiation treatment, so that metal iridium is loaded on the amorphous cobalt hydroxide nanosheets in the form of single atoms, to obtain mixture A;
[0050] In order to facilitate the ultraviolet light irradiation treatment, the present invention adopts Perfectlight PCX-50C multi-channel photochemical reaction system, and the illumination intensity of the ultraviolet light irradiation treatment is 80-120lx, and the illumination time is 0.5-1.5h.
[0051] Step 4, after solid-liquid separation of the mixture A, a solid component A is obtained, and the solid component A is sequentially washed and freeze-dried to obtain iridium single atom-modified cobalt hydroxide nanosheets;
[0052] It should be noted that the present invention does not limit the specific type of solid-liquid separation, as long as the solid component can be obtained. Preferably, the solid-liquid separation is performed by centrifugation at a speed of 8000 r / min for 1 min.
[0053] In the present invention, deionized water (DIW) is preferably used to wash the solid component A multiple times, and the washing is performed 5 times until the supernatant is clear, so as to remove impurities on the surface of the solid component A.
[0054] In order to avoid agglomeration of iridium single atom-modified cobalt hydroxide nanosheets during heating and drying, the present invention preferably adopts freeze drying to facilitate dispersion of the material in later use, and the freeze drying temperature is -45 to -25°C and the time is 12 to 36 hours.
[0055] Example 1
[0056] This embodiment provides a cobalt hydroxide nanosheet modified with a single iridium atom, and the preparation method thereof is as follows:
[0057] 1) Preparation of amorphous cobalt hydroxide nanosheets:
[0058] 1mmol Co(NO3)2·6H2O was dissolved in 100mL deionized water (DIW) and stirred vigorously at room temperature for 30min; then 3ml 1mol / L NaBH4 aqueous solution was added and stirred for 30min; the solid product was collected by centrifugation at 8000 rpm for 1min, washed several times with DIW, and freeze-dried to obtain amorphous cobalt hydroxide nanosheets.
[0059] 2) Preparation of iridium single atom-modified cobalt hydroxide nanosheets:
[0060] First, 1 mL of 5 mmol / L iridium chloride (IrCl3·xH2O) solution was added to 50 mL of aqueous solution containing 50 mg of amorphous cobalt hydroxide nanosheets, that is, in this embodiment, the ratio of iridium source to amorphous cobalt hydroxide nanosheets was 0.005 mmol:50 mg. Then, the mixture was irradiated with ultraviolet (UV) for 1 hour on a Perfectlight PCX-50C multi-channel photochemical reaction system (5WLED). After UV treatment, the solution was centrifuged, the sample was washed with DIW several times and freeze-dried to obtain iridium single atom-modified cobalt hydroxide nanosheets, which were named 1.46Ir-Co(OH) x Nanosheets (where 1.46 represents the mass percentage of Ir).
[0061] Example 2
[0062] This embodiment provides a cobalt hydroxide nanosheet modified with a single iridium atom, and the preparation method thereof is different from that of embodiment 1 only in that:
[0063] In this embodiment, when preparing iridium single atom modified cobalt hydroxide nanosheets, 2mL of 5mmol / L iridium chloride (IrCl3·xH2O) aqueous solution is added, that is, in this embodiment, the ratio of iridium source to amorphous cobalt hydroxide nanosheets is 0.01mmol:50mg.
[0064] The iridium single atom-modified cobalt hydroxide nanosheet obtained in this example is named 3.24Ir-Co(OH) x Nanosheets (where 3.24 represents the mass percentage of Ir).
[0065] Example 3
[0066] This embodiment provides a cobalt hydroxide nanosheet modified with a single iridium atom, and the preparation method thereof is different from that of embodiment 1 only in that:
[0067] In this embodiment, when preparing iridium single atom modified cobalt hydroxide nanosheets, 4mL of 5mmol / L iridium chloride (IrCl3·xH2O) aqueous solution is added, that is, in this embodiment, the ratio of iridium source to amorphous cobalt hydroxide nanosheets is 0.02mmol:50mg.
[0068] The iridium single atom-modified cobalt hydroxide nanosheet obtained in this example is named 6.17Ir-Co(OH) x Nanosheets (where 6.17 represents the mass percentage of Ir).
[0069] Example 4
[0070] This embodiment provides a cobalt hydroxide nanosheet modified with a single iridium atom, and the preparation method thereof is different from that of embodiment 1 only in that:
[0071] In this embodiment, when preparing iridium single atom modified cobalt hydroxide nanosheets, 6mL of 5mmol / L iridium chloride (IrCl3·xH2O) aqueous solution was added, that is, in this embodiment, the ratio of iridium source to amorphous cobalt hydroxide nanosheets was 0.03mmol:50mg.
[0072] The iridium single atom-modified cobalt hydroxide nanosheet obtained in this example is named 8.22Ir-Co(OH) x Nanosheets (wherein 8.22 represents the mass percentage of Ir).
[0073] Example 5
[0074] This embodiment provides a cobalt hydroxide nanosheet modified with a single iridium atom, and the preparation method thereof is different from that of embodiment 1 only in that:
[0075] In this embodiment, the ratio of amorphous cobalt hydroxide nanosheets to aqueous solvent A is 0.8 mg:1 mL;
[0076] The ratio of the iridium source to the amorphous cobalt hydroxide nanosheets in solution A is 0.005 mmol:50 mg;
[0077] The UV irradiation treatment time was 0.5 h;
[0078] The ratio of cobalt salt to aqueous solvent B is 0.8mmol:100mL;
[0079] The molar ratio of NaBH4 to cobalt salt is 3:1.
[0080] Example 6
[0081] This embodiment provides a cobalt hydroxide nanosheet modified with a single iridium atom, and the preparation method thereof is different from that of embodiment 1 only in that:
[0082] In this embodiment, the ratio of amorphous cobalt hydroxide nanosheets to aqueous solvent A is 1.2 mg: 1 mL;
[0083] The ratio of the iridium source to the amorphous cobalt hydroxide nanosheets in solution A is 0.03 mmol:50 mg;
[0084] The UV irradiation treatment time was 1.5 h;
[0085] Cobalt chloride is used as the cobalt salt, and the ratio of the cobalt salt to the aqueous solvent B is 1.2 mmol:100 mL;
[0086] The molar ratio of NaBH4 to cobalt salt is 5:1.
[0087] Example 7
[0088] This embodiment provides a cobalt hydroxide nanosheet modified with a single iridium atom, and the preparation method thereof is different from that of embodiment 1 only in that:
[0089] In this embodiment, the ratio of the iridium source to the amorphous cobalt hydroxide nanosheets in solution A is 0.015 mmol:50 mg.
[0090] Example 8
[0091] This embodiment provides a cobalt hydroxide nanosheet modified with a single iridium atom, and the preparation method thereof is different from that of embodiment 1 only in that:
[0092] In this embodiment, the ratio of the iridium source to the amorphous cobalt hydroxide nanosheets in solution A is 0.025 mmol:50 mg.
[0093] Comparative Example 1
[0094] Commercially available iridium oxide is used as the electrode catalyst material.
[0095] Comparative Example 2
[0096] The amorphous cobalt hydroxide nanosheets prepared in Example 1 are used as the electrode catalyst material.
[0097] Experimental part
[0098] (I) XRD test
[0099] The present invention takes the materials of Examples 1-4 and Comparative Example 2 as examples, and performs XRD tests respectively, and the test results are as follows: Figure 1 shown.
[0100] Depend on Figure 1 It can be seen that in the XRD patterns of the materials of Examples 1-4 and Comparative Example 2, diffraction peaks appear at 10.2°, 20.1°, 33.8° and 60.3°, corresponding to the (003), (006), (012) and (110) crystal planes of α-Co(OH)2 (JCPDS No. 46-0605), respectively, indicating that the materials of Examples 1-4 and Comparative Example 2 all have the structure of cobalt hydroxide nanosheets.
[0101] (ii) Scanning transmission electron microscope test
[0102] The present invention takes the material of Example 3 as an example, and performs a scanning transmission electron microscope test on it. The test results are as follows: Figure 2 and Figure 3 As shown, Figure 2 TEM image of the material of Example 3, Figure 3 This is an aberration-corrected high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) image of the material in Example 3.
[0103] from Figure 2 It can be clearly observed that the material of Example 3 has flexible ultrathin features of graphene-like nanosheets with curled edges (marked by arrows), and no Ir-based nanoparticles (NPs) are found.
[0104] from Figure 3 It can be seen that in the material of Example 3, Ir atoms are present in the amorphous Co(OH) x The nanosheets are dispersed in single-atom form. The high-contrast Ir atoms are bright spots marked by a series of circles.
[0105] (III) EDS spectrum test
[0106] The present invention takes the material of Example 3 as an example, and performs EDS spectrum test on it. The test results are as follows: Figure 4 shown.
[0107] from Figure 4It can be seen that in the material of Example 3, Ir atoms are uniformly distributed throughout the 6.17Ir-Co(OH) x On nanosheets.
[0108] (IV) Catalytic activity test
[0109] In this example, the materials of Examples 1-4, and Comparative Examples 1 and 2 are used as catalysts, and they are used as catalysts for electrocatalytic water decomposition and oxygen production to carry out oxygen evolution catalytic activity tests.
[0110] The oxygen evolution activity test conditions are as follows: a standard three-electrode system is used as the test system. First, a mixture of 4 mg of catalyst, 460 μL of ethanol and 40 μL of 5 wt% Nafion solution is ultrasonically dispersed to prepare a catalyst dispersion. Then, 5 μL of the catalyst dispersion is carefully dropped onto a polished glassy carbon electrode (GCE, diameter 0.3 cm) and then dried in air to obtain an ideal catalyst loading (mass loading of 0.566 mg cm -2 ). The GCE coated with catalyst was used as the working electrode, the carbon rod electrode as the counter electrode, the Ag / AgCl electrode as the reference electrode, the 1 mol / L KOH solution as the electrolyte, and the test instrument was the Shanghai Chenhua 760E electrochemical workstation. At room temperature 25°C, the obtained LSV for oxygen evolution is as follows Figure 5 The present invention uses overpotential (η, η = Potential - 1.23V) to evaluate the overall activity of the target electrocatalyst, and the current density is usually specified as 10 mA cm -2 The corresponding potential is the overpotential, which is used to compare the electrocatalytic activities of different catalysts.
[0111] Depend on Figure 5 It can be seen that in the LSV curves of the catalysts of Examples 1-4, the current density gradually increases with the increase of voltage. And among them, the overpotential of the catalyst of Example 1 is 0.286V, the overpotential of the catalyst of Example 2 is 0.274V, the overpotential of the catalyst of Example 3 is 0.251V, the overpotential of the catalyst of Example 4 is 0.266V, the overpotential of the catalyst of Comparative Example 1 is 0.291V, and the overpotential of the catalyst of Comparative Example 2 is 0.314V, that is, the overpotentials of the catalysts of Examples 1-4 are lower than the overpotentials of Comparative Examples 1 and 2, showing higher electrocatalytic activity, indicating that after the surface of amorphous cobalt hydroxide nanosheets is modified with iridium single atoms by the method of the present invention, it can efficiently catalyze the electrocatalytic water decomposition and oxygen production and evolution reaction, and its catalytic performance is better than commercially available iridium oxide and a single amorphous cobalt hydroxide nanosheet.
[0112] and Figure 5The experimental results show that in order to make the material prepared by the present invention obtain better catalytic performance, the loading amount of iridium single atoms cannot be too large or too small. Preferably, it is adjusted within a certain range, such as the usage ratio of iridium source to amorphous cobalt hydroxide nanosheets in solution A is 0.015-0.025mmol:50mg.
[0113] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for preparing cobalt hydroxide nanosheets modified with iridium single atoms, characterized in that: The following steps are involved: Step 1, using amorphous cobalt hydroxide nanosheets as a precursor, and uniformly dispersing them in a water solvent A to obtain a solution A; Step 2, adding an iridium source to solution A and mixing evenly to obtain solution B; Step 3, subjecting the solution B to ultraviolet irradiation treatment, so that the metal iridium is loaded on the amorphous cobalt hydroxide nanosheets in the form of single atoms, to obtain a mixture A; Step 4, after solid-liquid separation of the mixture A, a solid component A is obtained, and the solid component A is sequentially washed and freeze-dried to obtain the iridium single atom-modified cobalt hydroxide nanosheet; The usage ratio of the iridium source to the amorphous cobalt hydroxide nanosheets in the solution A is 0.005-0.03 mmol:50 mg; The ultraviolet light irradiation treatment time is 0.5 to 1.5 hours.
2. The preparation method according to claim 1, characterized in that The usage ratio of the amorphous cobalt hydroxide nanosheets to the water solvent A is 0.8-1.2 mg:1 mL.
3. The preparation method according to claim 1, characterized in that: The iridium source is iridium chloride.
4. The preparation method according to claim 1, characterized in that: The amorphous cobalt hydroxide nanosheets are prepared by the following steps: S1, uniformly dispersing the cobalt salt in the aqueous solvent B, then adding NaBH4 and mixing evenly to obtain a mixture B; S2, separating the mixture B into solid and liquid to obtain a solid component B, washing the solid component B and freeze-drying it to obtain the amorphous cobalt hydroxide nanosheets.
5. The preparation method according to claim 4, characterized in that: The cobalt salt is cobalt chloride or cobalt nitrate.
6. The preparation method according to claim 4, characterized in that: The ratio of the cobalt salt to the aqueous solvent B is 0.8-1.2 mmol:100 mL; The molar ratio of the NaBH4 to the cobalt salt is 3 to 5:
1.
7. An iridium single atom-modified cobalt hydroxide nanosheet prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The invention comprises an amorphous cobalt hydroxide nanosheet and an iridium single atom on the amorphous cobalt hydroxide nanosheet.
8. Use of the iridium single atom-modified cobalt hydroxide nanosheets according to claim 7 in a catalyst for electrocatalytic water decomposition and oxygen production.
Citation Information
Patent Citations
Preparation method of supported reduction-state noble metal catalyst
CN108940383A
Nanometer material with precious metal single atoms dispersed on surface of non-precious metal substrate and preparation method and application of nanometer material
CN114525521A
Cobalt-doped modified porous nitrogen-doped carbon nanosheet as well as preparation method and application thereof
CN117712394A
Nano-material with noble metal single atoms dispersed on surface of non-noble metal substrate and preparation method and use of nano-material
WO2023193537A1
